Neuroanatomy of the vertebral column of Vegasaurus molyi (Elasmosauridae) with comments on the cervico-dorsal limit in plesiosaurs - O'gorman, Jose Patricio; Fernández, Marta S. (Cretaceous Research)
The evolution of the axial skeleton of vertebrates, particularly regionalization and the changes in the limits of each region is yet to be completely understood. The features of this process are more difficult to follow in groups with strong changes in the number of vertebrae as is the case of plesiosaurs. In this work we record the osseous correlates of the nervous system housed in the neural channel along the vertebral column of the elasmosaurid Vegasaurus molyi, from the lower Maastrichtian levels of the Snow Hill Island Formation (Antarctica). The new data allows inference of the position of the brachial plexus (i.e. the innervation of the pectoral girdle and anterior limbs), which in turn allows identification of the position of the pectoral girdle and the homology of the transitional “pectoral” region and the anterior dorsal (=trunk) vertebrae. The results indicate that in Vegasaurus molyi the pectoral girdle is at the level of the so called “pectoral” region, and that the pectoral region is homologous to the anterior trunk vertebrae of other Sauropsida. Additionally, the comparison with other published results of polycotylids showing differences with V. molyi suggesting an interesting difference in the pattern of vertebral column regionalization among plesiosaurs. Fil: O'gorman, Jose Patricio. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina Fil: Fernández, Marta S. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina